Effect of Heat Stress on Flower Anatomy of Heat Tolerance and Susceptible Chickpea (Cicer arietinum L.) Genotypes by Scanning Electron Microscopy - Pipaliya, H. R.; Gajera, H. P.; Hirpara, D. G.; Khunt, K. R.; Bhalara, R. L. (International Journal of Bio-resource and Stress Management, 2020)
With increasing globally averaged temperature of the air above the earth’s surface would raise by 1.4- 5.8 °C over the next 100 years and its negative impact on reproductive stage is thus increasingly becoming a serious constraint to chickpea production in India. The present study was undertaken to exogenous application of salicylic acid at flowering stage in four chickpea genotypes (ICC-4958, GG-2, ICC-4567 and GJG-5) under normal sowing (14th November, 2018) and late sowing (12th December, 2018). Chickpea has a strong indeterminate growth habit, and generally it produces many flowers, but only 50% to 80% of these develop into mature pods due to the failure of pod set and pod abortion. A few days of exposure to high temperatures (30-35°C) causes heavy yield losses through accelerating flower drop and pod abortion. Heat stress inhibited pollen function and pollen tube growth more in the heat susceptible genotypes (ICC-4567 and GJG-5) than in the tolerant genotypes (ICC-4958 and GG-2). The exogenous application of SA at 50% flowering stage in late sowing showed that the significant difference was found in number of flowers per plant and there was no significant difference found in number of flowers per plant during normal sowing. In all genotypes number of flower plant-1 increased after spraying 100 ppm SA as compared to control. Heat stress inhibited pollen function and pollen tube growth more in the sensitive genotypes than in the tolerant genotypes.